Sexual Dimorphism in Autoimmune Disorders - Gupta, PD (Clinical Journal of Obstetrics and Gynecology, 2024)
Sexual dimorphism exists in Homo sapiens in many systems. Lately, it was found that it also exists in autoimmune disorders. Generally, it was known that the two genders in humans have different endocrine systems, and therefore hormone hormone-regulated systems show sexual dimorphism. However, in the case of autoimmune disorders, it is not due to directly on hormonal milieu but depends on X-chromosome inactivation in males. Whereas every cell in a woman’s body produces Xist; this ribonucleoprotein contains about 81 proteins. This chromosomal inactivation in males and formation of Xist ribonucloprotein in females is responsible for sexual dimorphism in autoimmune disorders in humans.